Impact of time from symptom onset on the diagnostic performance of high-sensitivity cardiac troponin for type 1 myocardial infarction. (3rd October 2022) - Lowry, M; Doudesis, D; Kimenai, D; Bularga, A; Taggart, C; Wereski, R; Ferry, A; Stewart, S; Tuck, C; Lee, K; Chapman, A; Shah, A; et al.
Abstract: Background: High-sensitivity cardiac troponin has enabled the rapid rule-out and rule-in of myocardial infarction at presentation. However, increases in cardiac troponin may not be detectable early after symptom onset, and uncertainty remains as to how time of symptom onset influences diagnostic performance. Purpose: To evaluate the impact of time from symptom onset on the diagnostic performance of high-sensitivity cardiac troponin for type 1 myocardial infarction. Methods: In a secondary analysis of a prospective multicentre randomised controlled trial of consecutive patients with suspected acute coronary syndrome, we evaluated the diagnostic performance of high-sensitivity cardiac troponin I measurements at presentation stratified by time of symptom onset to blood sampling. Diagnostic performance was evaluated in four groups (≤3 hours, 4–6 hours, 7–12 hours and >12 hours from symptom onset) for recommended thresholds to rule-out (sex-specific 99th centile and optimised threshold [64 ng/L]) type 1 myocardial infarction. Results: This analysis included 41, 104 patients (median 60 [interquartile range 49–74] years, 46% female) of which 12, 595 (31%), 10, 298 (25%), 7, 171 (17%) and 11, 040 (27%) presented ≤3 hours, 4–6 hours, 7–12 hours and >12 hours, respectively. Type 1 myocardial infarction was the adjudicated diagnosis in 3, 692 (9%) patients. For the rule-out of type 1 myocardial infarction, sensitivity was highest in those tested 7–12 hours from symptom onset and lowest in those tested ≤3 hours. In early presenters, a threshold of <2 ng/L had greater sensitivity and negative predictive value (99.4% [95% CI 98.9 to 99.7%] and 99.7% [95% CI 99.5 to 99.9%]) compared to <5 ng/L (96.7% [95% CI 95.7 to 97.6%] and 99.3% [95% CI 99.1 to 99.5%], respectively). In those tested >3 hrs from symptom onset, the sensitivity and negative predictive value for both thresholds were similar, but a threshold of <5 ng/L correctly ruled out more patients (60% [17, 056/28, 506] versus 29% [8, 316/28, 506]). For the rule-in of myocardial infarction, the sensitivity of the 99th centile and 64 ng/L was lowest in patients tested within 3 hours (71.7% [95% CI 69.3 to 74.1%] and 46.5% [95% CI 44.1 to 49.2%], respectively), and increased in those tested later from symptom onset. The specificity and positive predictive value were highest when testing was performed 7–12 hours from symptom onset for the sex-specific 99th centile (92.4% [95% CI 91.8 to 93.0%] and 51.3% [95% CI 48.2–54.5%]) and 64 ng/L (96.2% [95% CI 95.7 to 96.7%] and 61.2% [95% CI 57.3 to 65.2%]). Conclusions: The diagnostic performance of cardiac troponin for myocardial infarction is strongly influenced by the time from symptom onset to testing. In early presenters the limit of detection may facilitate immediate rule-out of myocardial infarction, but otherwise testing at least 3 hours from symptom onset is needed with the optimal time to rule-in myocardial infarction being 7–12 hours from the onset of symptoms. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): British Heart Foundation (BHF)Medical Research council UK (MRC)